2022
DOI: 10.1186/s12906-022-03743-6
|View full text |Cite
|
Sign up to set email alerts
|

Cistanche tubulosa phenylethanoid glycosides suppressed adipogenesis in 3T3-L1 adipocytes and improved obesity and insulin resistance in high-fat diet induced obese mice

Abstract: Background Cistanche tubulosa is an editable and medicinal traditional Chinese herb and phenylethanoid glycosides are its major components, which have shown various beneficial effects such as anti-tumor, anti-oxidant and neuroprotective activities. However, the anti-obesity effect of C. tubulosa phenylethanoid glycosides (CTPG) and their regulatory effect on gut microbiota are still unclear. In the present study, we investigated its anti-obesity effect and regulatory effect on gut microbiota by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Additionally, they could also be utilized as diagnostic and prognostic markers. [30][31][32][33]. IRS1, a pivotal component of the insulin signaling pathway, along with GLUT4, a significant glucose transporter, are recognized for their contributions to maintaining glucose homeostasis and insulin sensitivity [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they could also be utilized as diagnostic and prognostic markers. [30][31][32][33]. IRS1, a pivotal component of the insulin signaling pathway, along with GLUT4, a significant glucose transporter, are recognized for their contributions to maintaining glucose homeostasis and insulin sensitivity [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…M. timonensis is a recently described and poorly characterized species related to bacteria from the Faecalicatena genus from the Lachnospiraceae family [85]. The administration of plant-derived bioactive phenylethanoid glycosides increased the abundance of M. timonensis, concurrently decreasing total Ch, LDL, and HDL levels in a mouse model of obesity, suggesting a possible link between the species and circulating lipids [86]. In the current study, participants who reported a higher consumption of fibrerich foods such as fruits and legumes had a low relative abundance of this species.…”
Section: Taxa Associated With Serum Lipid Levelsmentioning
confidence: 99%
“…Among the identified hydroxybenzoic and hydroxycinnamic acids, flavones, and flavone glycosides [8][9][10], phenylethanoid glycosides (PGs) represent the most understudied phenolic group found in T. montanum extracts. The latest studies show that PGs are promising neuroprotective [11], anticancer [12], anti-obesity [13], anti-inflammatory [14], and antibacterial [15] agents. The highlighted antiviral properties of PGs, which act as natural inhibitors of SARS-CoV-2 protease, are already being used in China for COVID-19 treatment in the form of a patented TCM formulation-Lianhua Qingwen capsules [16,17].…”
Section: Introductionmentioning
confidence: 99%